THE ROLE AND IMPORTANCE OF THE GMINA IN TOURISM POLICY IN POLAND - Hyski, Marcin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the article is to indicate the role and importance of the gmina as a special institution of the Polish tourism system in shaping the local tourism policy of the area. The article presents the concept and objectives of tourism policy, and describes the various entities of tourism policy in Poland and their tasks. Against this background, the article captures the gmina's tasks in the sphere of tourism together with the instruments of tourism policy that are at its disposal. The article uses a descriptive and qualitative analysis method that allowed to identify the role of the gmina in the tourism system in Poland. The analysis includes literature in the field of economic sciences, based additionally on legal acts related to the discussed issue. As an institution of the tourism system, the gmina has the task of satisfying the needs of the local community and stimulating local development, thanks to which it plays an important role in shaping the local tourism policy. The gmina has a wide range of activities on the local tourist economy. It should be emphasized that this is not an individual task of the gmina, although there is no doubt that it has a wide range of opportunities to influence this sphere of social and economic life. Tourism policy should be undertaken and implemented in cooperation with private sector entities conducting tourist activity, but also entities from outside the tourism industry (so-called paratourism entities) and their organizations and associations. Tourism policy should also be implemented together with other local government units, the area of which is covered by an initiative in the field of tourism development, including also higher-level entities (such as poviats and voivodships), as well as with local and regional tourist organizations and other non-governmental organizations.